MLS Little Dreamer 2018 at SJK (C) Pei Chai Kuantan - Kang, Mei Feng (2018)
17th of October 2018 - The Mandarin Language Society (MLS) of University Malaysia Pahang (UMP) successfully organised the Little Dreamer 2018 program at SJK(C) Pei Chai, Kuantan, Pahang .